LANDSCAPE GEOMORPHOLOGICAL EVOLUTION AND COASTAL CHANGES: A CASE STUDY OF COASTAL EVOLUTION IN THE WESTERN PATRAIKOS GULF AREA, WESTERN GREECE - Alevizos, G.; Stamatopoulos, L. (Bulletin of the Geological Society of Greece, 2016)
Geological and geomorphological research has been carried out in the western part of the south coast of Patraikos Gulf and the findings were studied in relation to archaeological remains found in the same area. The characteristics of the archaeological findings and the stratigraphical record and the deposits in which they are contained, may originate their source, transportation way and age. The artifacts were contained in fluvial and alluvial deposits under the present land surface. Their age was estimated by archaeologists to be between 7th century BC and 4th century AC. Geomorphology and archaeology have strong historical and methodological links and can provide information about the processes and extent of environmental changes. They also provide the tools for analysing sedimentation rates, relative chronology and geomorphological evaluation of the particular archaeological site as well as clues for land-surface development, paleoenvironmental and climatic conditions. Sediments indicating considerable climatic changes in current humid areas are alluvial deposits of considerable thickness, covering areas with human activity. There is a close correlation, as shown by the archaeological findings between climatic and environmental fluctuations. Since when there is a transition in climatic conditions causing changes in hydrologic conditions with ensuing geomorphological instability and burying the structures